Utilizing Social Media in EFL Blended Learning: Challenges, Strategies and Opportunities - Martunis, Martunis; Muntasir, Muntasir; Azmy, Khairul (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
In English as a Foreign Language (EFL) classroom settings, the rapid evolution of digital technology has had a substantial impact on educational methodologies. This paper investigates the potential of social media to improve EFL blended learning instruction, with a particular emphasis on the higher education context of Indonesia. Innovative tools for promoting student engagement, motivation, and autonomous learning are available on social media platforms, including Facebook, Twitter, and YouTube. Nevertheless, the implementation of these social media platforms also presents obstacles, such as potential privacy concerns, distractions, and unequal access to digital resources. This investigation examines the current body of literature regarding the utilization of social media in EFL blended learning purposes. Social media can significantly improve the EFL learning experience by offering flexible, interactive, and engaging learning opportunities when strategically implemented, according to the results. The paper concludes with suggestions for policymakers and educators to facilitate the successful integration of social media into EFL education, thereby guaranteeing that technological advancements have a beneficial impact on student learning outcomes.the other.